1990
DOI: 10.2307/3282811
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Effect of Larval Schistosoma mansoni Excretory-Secretory Products on Phagocytosis-Stimulated Superoxide Production in Hemocytes from Biomphalaria glabrata

Abstract: The in vitro production of the reactive oxygen metabolite superoxide (O2-) was confirmed in hemocytes from the schistosome intermediate host Biomphalaria glabrata. Active forms of the enzyme superoxide dismutase (SOD) inhibited reduction of nitroblue tetrazolium (NBT) to formazan in cells that had phagocytozed zymosan particles, whereas an inactivated form of SOD did not. Moreover, based on the prevalence of O2(-)-positive hemocytes and the relative intensity of NBT staining reactions, hemocytes from the Schis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 33 publications
3
32
0
Order By: Relevance
“…chemotaxis, chemiluminescence), natural killer cells and T lymphocytes (Kharazami, 1991;Kharazami & Nielsen, 1991). Molluscan parasites also produce protein factors that suppress haemocyte activities such as chemokinesis and superoxide production (Connors & Yoshino, 1990;Lodes & Yoshino, 1990; Van der Knapp & Loker, 1990).…”
Section: Introductionmentioning
confidence: 98%
“…chemotaxis, chemiluminescence), natural killer cells and T lymphocytes (Kharazami, 1991;Kharazami & Nielsen, 1991). Molluscan parasites also produce protein factors that suppress haemocyte activities such as chemokinesis and superoxide production (Connors & Yoshino, 1990;Lodes & Yoshino, 1990; Van der Knapp & Loker, 1990).…”
Section: Introductionmentioning
confidence: 98%
“…ESPs from platyhelminths generally consist of antioxidant enzymes, protease inhibitors, cysteine proteases, small HSPs, glycolytic enzymes, mucins, calcium, ion-binding proteins and other unknown proteins (Connors et al 1991;Guillou et al 2007;Humphries and Yoshino 2008;Lodes and Yoshino 1989;Roger et al 2008;Wu et al 2009;Zelck and Von Janowsky 2004). These parasite-derived molecules can influence the behaviour of B. glabrata defence cells (haemocytes) by affecting their motility, adhesion, ability to phagocytose or encapsulate large antigens and produce reactive oxygen species and intracellular nitric oxide (NO; Connors et al 1991;Connors and Yoshino 1990;Humbert and Coustau 2001;Loker et al 1992;Lodes and Yoshino 1990;Zahoor et al 2009). Laboratory strains of B. glabrata exist that are either resistant or susceptible to S. mansoni infection; unlike in the susceptible strain, in the resistant strain the parasite is killed before it develops fully into a mother sporocyst.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that living P marinus not only fails to generate LuCL upon phagocytosis, but also can inhibit LuCL produced intracellularly in response to stimulatory agents such as zymosan. The identity of the agent(s) produced by P marinus responsible for this apparent reduction in ROS generation remains unknown, butit is interesting to note that one ofthe functions of excretory/secretory proteins produced by the parasite Schistosoma mansoni is to suppress 02-production by the hemocytes of its molluscan host, Biomphalaria glabrata (Connors and Yoshino, 1990;Connors, Lodes and Yoshino, 1991).…”
Section: Ros Responses Elicited By Pathogensmentioning
confidence: 99%